Determinação do coeficiente de transferência de calor em um aço ABNT/SAE 1045 através do Ensaio Jominy - Petersen, Jefferson Ricardo Bilheri (2012)
This work presents a numerical-experimental correlation of the factors that may influence the hardenability of SAE 1045 steel subjected to the Jominy end quench test at austenitizing temperature of 850 °C. This correlation was made by calculating the heat transfer coefficient and its phase‟s presents during the cooling of the specimen. These calculations were obtained based on thermal analysis of the test, through the cooling rates. A thermocouple was installed near from the edge of the specimen to obtain the cooling temperature curves. Based on these informations were estimated uncertainties of measurement temperature ± 23 °C for an evaluation of the reproducibility of the process, even an error of ± 10.3 °C. During the Jominy test, should be considered parameters such as hydraulic pressure suitable austenitizing temperature with a tolerance of ± 6 °C, temperature and water flow. These parameters change the phase heat transfer, and also the flux density and therefore the heat transfer coefficient of heat. It was determined the variation of the heat transfer coefficient versus time h=f(t), and the average value is close to theorycal value, which is approximately 15.3 kW/m2.K